MAGNETIC BASEMENT MODELLING USING MAGB_INV IN THE HYDROCARBON POTENTIALAREA OF THE BANYUMAS BASIN, CENTRAL JAVA - Mardita, Devina
Sedimentary basins are closely related to magnetic bedrock which contains potential hydrocarbon information. The Banyumas Basin has hydrocarbon potential with the discovery of oil seeps on the surface. Magnetic bedrock modeling of the Banyumas Basin is one of the main objectives of this study. The MagB_Inv program is a MATLAB program that is useful for obtaining 2D and 3D models of magnetic bedrock by processing large amounts of data and performing fast and accurate calculations. Calculations in this program use the Fourier Transform and high cut-filter to avoid high frequency instability. In the Banyumas Basin area, the MagB_Inv program is applied by entering the total magnetic anomaly value. The average depth obtained from the modeling is 7.99 km, the maximum depth is 10.89 km, and the minimum depth is 6.11 km. The Banyumas Basin area has potential reserves of hydrocarbons with a subsurface elevation pattern identified by the Old Andesite Formation as magnetic bedrock with its upper boundary bordering the source rocks of the Kalipucang Formation and Pemali Formation at Miocene age